Effectiveness of immunoglobulin prophylaxis in reducing clinical complications of hematopoietic stem cell transplantation: a systematic review and meta‐analysis. Issue 10 (16th May 2018) - Ahn, Hilalion; Tay, Jason; Shea, Beverley; Hutton, Brian; Shorr, Risa; Knoll, Greg A.; Cameron, Donald William; Cowan, Juthaporn
Abstract : BACKGROUND: Prophylactic immunoglobulin has been used with varying efficacy to reduce complications in hematopoietic stem cell transplant recipients. STUDY DESIGN AND METHODS: A systematic review and meta‐analysis was conducted of randomized controlled trials that assessed clinical outcomes (overall survival, transplant‐related mortality, graft‐versus‐host disease [GVHD], veno‐occlusive disease [VOD], interstitial pneumonitis, disease relapse, cytomegalovirus [CMV] infection and disease, non‐CMV infection) of immunoglobulin prophylaxis versus placebo in hematopoietic stem cell transplant recipients. MEDLINE, EMBASE, EBM Reviews, and the Cochrane Central Register of Controlled Trials were searched up to June 2017. Quality of included studies and outcomes were evaluated via Risk of Bias assessment and Grading of Recommendations, Assessment, Development and Evaluation criteria, respectively. RESULTS: Of 899 citations screened, 27 studies (n = 3934) were included. Immunoglobulin prophylaxis had no impact on survival (risk ratio [RR], 0.94; 95% confidence interval [CI], 0.88‐1.01; 11 studies, n = 1962) but decreased risk of acute GVHD (RR, 0.78; 95% CI, 0.65‐0.94; eight studies, n = 1097) and CMV disease (RR, 0.52; 95% CI, 0.28‐0.97; two studies, n = 167). Meta‐analysis revealed increased risk of VOD (RR, 3.04; 95% CI, 1.10‐8.41; three studies, n = 384) and disease relapse (RR, 1.26; 95% CI, 1.07‐1.49; seven studies, n = 1647). Other outcomes were small in sample size or nonsignificant. Results should be interpreted cautiously given the low quality of studies and evidence of outcomes. CONCLUSION: Immunoglobulin prophylaxis did not have a significant effect on survival. Positive clinical effects were shown for acute GVHD and CMV disease and negative effects against VOD and disease relapse. No studies examined the effect of immunoglobulin treatment in hypogammaglobulinemic patients despite current guidelines, warranting further studies in this population.